Community Mental Health: Psychosocial teams and public policies in the intervention of people with addictions - Daniela Olivares-Aising; Universidad Austral de Chile - Universidad de la Frontera; María del Valle Barrera; Universidad Austral de Chile (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2019)
In Chile, the  National Plan of Mental Health and Psychiatry from 2001, shapes the public policy in its area. So far, the impact that this Plan has had on decreasing alcohol and drug abuse has been scarce. Here we argue why the evidence obtained fail to feedback public policy to modify the lean results. This document stresses the hierarchical and linear traditional evaluation methods for public policy that only quantify and minimize the problem. We performed a participative evaluation with three psychosocial work teams in Mental Health, applying the Needs and Satisfactors Matrix and interviewing key informants. From a qualitative epistemic perspective, that is interpretationist and situated, using the Human Scale Development and Grounded Theory as theoretical and methodological frames of reference,we conclude that there is a lack of a social theory that explain the phenomenon, the precarious working and social conditions and the epistemic contradiction in the everyday work.